2016
DOI: 10.1177/2331216516639234
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Swedish Hearing Handicap Inventory for the Elderly (Screening Version) and Evaluation of Its Effect in Hearing Aid Rehabilitation

Abstract: Self-reports of subjective hearing difficulties by people with hearing loss may be a useful complement to audiometry in hearing aid rehabilitation. To be useful, such self-reports need to be reliable. This study investigated the reliability and the validity of the Swedish Hearing Handicap Inventory for the Elderly (Screening Version; HHIE-S). Sixty-nine participants completed a questionnaire before hearing aid rehabilitation. Of these individuals, 49 completed hearing aid rehabilitation (aged between 23 and 94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
(48 reference statements)
1
15
0
2
Order By: Relevance
“…The Cronbach's alpha score for the HHIE-ST, the original version, the Japanese version and the Swedish version are 0.94, 0.82, 0.91 and 0.77, respectively. (22,26,48) Regarding HHIE-ST scores and demographic data correlations, we found that mean scores were signi cantly correlated with age group, with older individuals having higher scores (p < 0.001). There was no signi cant difference of HHIE-ST scores between sex or area of residence.…”
Section: Discussionmentioning
confidence: 81%
“…The Cronbach's alpha score for the HHIE-ST, the original version, the Japanese version and the Swedish version are 0.94, 0.82, 0.91 and 0.77, respectively. (22,26,48) Regarding HHIE-ST scores and demographic data correlations, we found that mean scores were signi cantly correlated with age group, with older individuals having higher scores (p < 0.001). There was no signi cant difference of HHIE-ST scores between sex or area of residence.…”
Section: Discussionmentioning
confidence: 81%
“…For our study, we found that the reliability was very good for our Thai version and that our internal consistency was higher than that achieved by the Swedish version and comparable to that of the original version. The Cronbach’s alpha score for the HHIE-ST, the original version, the Japanese version and the Swedish version are 0.94, 0.82, 0.91 and 0.77, respectively [ 23 , 27 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-assessed hearing problems were measured with the HHIE questionnaire, developed by Ventry and Weinstein (1982), and translated and validated in Swedish by € Oberg (2016). An adapted version of the OVQ questionnaire was used to study the participants' experience of their own voice.…”
Section: Questionnaires and Proceduresmentioning
confidence: 99%